PERAN TEKNOLOGI INFORMASI DALAM AKTIFITAS DAKWAH: Menelusuri Signifikansi Dakwah Online - Rusli, Rusli (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2013)
This paper  deals with the role of information technology in da 'wa   acivities. It concludes  that  because  of the spread  of Internet, online da'wa as a kind of new model of Islamic preaching emerges. This kind of da'wa focused on the socialization that includes process of al-ta 'aruf (acquaintance) and   al-ta'aluf (harmony) with the target of object of Islamic preaching ( al-mad' u ). This is carried out based on the three levels of online interaction, which includes spreading, participation and mobilization.